Personality differences between native and invasive populations of the eastern gray squirrel - Margaret R. Merz; Claudia Tranquillo; Francesca Santicchia; Lucas A. Wauters; Alessio Mortelliti (Mammalian Biology, 2026)
Invasive alien species are a major threat to global biodiversity, thus recent work has aimed to identify traits of successful invaders to better inform management efforts and predictions of future invasions. Personality and intraspecific behavioral variation are important characteristics that may mediate individuals’ and species’ invasion success. However, to the best of our knowledge, no study to date has looked at the personality differences between an invasive species in its native and invasive ranges. Here, we filled this gap by studying the sociality and self-grooming behavior of eastern gray squirrels ( Sciurus carolinensis ) in their native range in Northeastern USA and in their invasive range in Italy. We used the open field and mirror-image stimulation tests to assess the personality of 466 unique gray squirrels, including 271 individuals from the native population and 195 from the invasive population. We found that both the distribution and the median value of sociality significantly differed between populations, with a higher median value of sociality among invasive squirrels, while the distribution and median of self-grooming, a proxy for stress-coping ability, did not significantly differ between populations. Overall, we demonstrate that certain personality traits differ between native and invasive populations, highlighting the importance of considering intraspecific behavioral diversity for the prediction and management of invasive alien species. We urge further work to elucidate the mechanisms behind such personality differences.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Intraspecific and environmental variation mediate seed finding effectiveness among scatter‐hoarding small mammals - Margaret R. Merz; Sydne Record; Alessio Mortelliti (Ecology, 2026)
About half of all plant species rely on animals such as scatter‐hoarding small mammals for seed dispersal. These plants include many keystone species for which small mammals are key primary and secondary dispersal agents as well as seed predators. To predict the regeneration and movement of such plant species, we must understand small mammal seed finding effectiveness, or how many seeds they find and how quickly they find them. The ability of small mammals to find seeds is a critical first step of the seed dispersal or predation process, upon which all other steps depend, but it has received relatively little attention. With a field experiment, we aimed to fill this gap, uncovering environmental, demographic, and intraspecific predictors of seed finding effectiveness. We assayed the behavior of 1296 southern red‐backed voles ( Myodes gapperi ) and 1053 deer mice ( Peromyscus maniculatus ) to identify and mark individuals with different personalities. Afterward, we established experimental seed stations with white pine ( Pinus strobus ) seeds and red oak ( Quercus rubra ) acorns scattered on the forest floor. We recorded the foraging behavior of 23 voles and 18 mice with known personality and assessed the effects of seed availability, environmental factors, small mammal density, and personality on their proportion of found seeds, seed finding rates, and probability of dispersing found seeds. More timid and docile voles found fewer white pine seeds and found them slower. Voles found more red oak acorns and found them more quickly when small mammal density was higher, and individual seed finding rates increased with white pine seed availability. At the community level, forest treatment and small mammal species richness influenced the number of found and removed seeds. These results contribute to identifying the factors that influence seed finding effectiveness, enhancing our understanding of this pivotal first step of seed predation and dispersal. We highlight the effect of personality on the quantity of found seeds and underscore the importance of considering behavioral diversity when predicting seed dispersal and predation rates.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Emergence of heavy tails in streamflow distributions: the role of spatial rainfall variability - H.-J. Wang; R. Merz; S. Yang; L. Tarasova; S. Basso (Advances in Water Resources, 2023)

Increased endothelial microparticles and oxidative stress at extreme altitude - Jacqueline Pichler Hefti; Alexander Leichtle; Monika Stutz; Urs Hefti; Thomas Geiser; Andreas R. Huber; Tobias M. Merz (European Journal of Applied Physiology, 2016)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Time-varying signal analysis to detect high-altitude periodic breathing in climbers ascending to extreme altitude - A. Garde; B. F. Giraldo; R. Jané; T. D. Latshang; A. J. Turk; T. Hess; M. M. Bosch; D. Barthelmes; T. M. Merz; J. Pichler Hefti; O. D. Schoch; K. E. Bloch (Medical & Biological Engineering & Computing, 2015)

Dependence between flood peaks and volumes: a case study on climate and hydrological controls - L. Gaál; J. Szolgay; S. Kohnová; K. Hlavčová; J. Parajka; A. Viglione; R. Merz; G. Blöschl (Hydrological Sciences Journal, 2015)

Review: Powdery Scab of Potato—Increased Knowledge of Pathogen Biology and Disease Epidemiology for Effective Disease Management - U. Merz; R. E. Falloon (Potato Research, 2009)

The potential for the Rapid Screening of Potato Cultivars (Solanum tuberosum) for Resistance to Powdery Scab (Spongospora subterranea) using a Laboratory Bioassay - U. Merz; V. Martinez; R. Schwärzel (European Journal of Plant Pathology, 2004)

Chaetae and mechanical function: tools no Metazoan class should be without - Sarah A. Woodin; Rachel A. Merz; Florence M. Thomas; Deirdre R. Edwards; Irene L. Garcia (Hydrobiologia, 2003)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)